Pengaruh Globalisasi Terhadap Nilai Nasionalisme Generasi Muda - Efendi Agus; Zulfahmi Zulfahmi (Iuris Studia: Jurnal Kajian Hukum, 2021)
At this time, how easy it is for people to communicate over long distances, not only between cities but between countries which are very far away. Even now, communication tools are growing rapidly and modern. In the past, communication was carried out by writing letters and took a long time, but now communication tools are increasingly sophisticated, namely by using the telephone. That is a picture of life today, a life that is all global in various aspects or dimensions of human life. This is what is called globalization (globalization). This writing uses normative juridical legal research methods (normative research). The nature of this research is descriptive, which aims to provide an overview of the influence of globalization on the value of the young generation's nationalism. Sources of research data are in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data collection method was carried out using document study techniques, which were analyzed using qualitative analysis techniques. In this modern era, globalization is very influential and even becomes a necessity to achieve a goal whether it is positive or negative and how to access it is also very easy to use existing facilities such as Android and so on. Globalization has had a huge impact on the dimensions of human life, because globalization is a process of internationalization of all the links of modern society. So that there are various impacts, especially on the social aspects, the positive impact of advances in communication and information technology makes it easier for humans to interact with other humans. While the negative impact, the number of values and culture of society that have changed by imitating or applying selectively